Suckermouth Catfish (Pterygoplichthys pardalis) In Wajo Regency, South Sulawesi Province: The Heavy Metal Content of Lead (Pb), Mercury (Hg) and Arsenic (As) (Agrikan Jurnal Agribisnis Perikanan, 2021)
Suckermouth catfish (Pterygoplichthys pardalis) is a type of foreign fish (South America) which is prohibited from entering Indonesia because it can endanger ecosystems and the aquatic environment by its invasive nature. The existence of janitor fish threatens the sustainability of the endemic fish of Tempe Lake in Wajo Regency. Until now, there has been no study regarding the quality and food safety for the use of suckermouth catfish in the regency. This study aims to analyzed the heavy metal content of lead (Pb), mercury (Hg) and arsenic (As) of janitor fish in Wajo Regency. Samples of janitor fish were taken from three districts in Wajo Regency used a purpossive sampling technique. Analysis of Pb, Hg and As metals on meat, scales/skin, and bones/fins of suckermouth catfish, refers to SNI 2354.5: 2011, SNI 2354.6-2016 and SNI 01-4866-1998. The results show that suckermouth catfish from the three districts are not contains Pb but contains Hg and As which do not exceed the requirements for metal contamination content limits based on SNI 2729: 2013 concerning requirements for quality and safety of fresh fish
Keywords: Ikan sapu-sapu; Wajo; Logam berat; Timbal; Merkuri; Arsen